Endowment of Haram Money and its Contemporary Applications: A Comparative Jurisprudence Study - Shalah, Mohammad Motlaq Hamdan (Dirasat: Shari'a and Law Sciences, 2021)
This study deals with the issue of endowment of unlawful money and its contemporary applications by clarifying the meaning of endowment, and clarifying what is related to the meaning of unlawful money, and its divisions. Prohibited money is divided into two parts: prohibited for its own sake, such as alcohol, and prohibited for earning it, which was originally permissible, except that the method of acquiring it has been forbidden by Allah. The study also deals with the legal reality of haram money, in terms of the lack of legitimate ownership of haram money. Then the study shows the effect of haram money on the issue of endowment by considering the endowment from the total of alms, and the forbidden money of the kind that should be disposed of because the legal ownership of it was not fulfilled.The researcher concluded by dividing the disposal of unlawful money via endowment into two forms. The first is endowment of unlawful money on the basis of kinship, as money in this case falls within legal ownership. The second is endowment of haram money as a form of disposal, taking into consideration that the criterion in the difference between these two forms is that money in this case falls within legal ownership. The study showed contemporary applications for endowing haram money, such as the Islamic Development Bank; and solutions to dealing with haram money for the public interest by collecting it in a special account to spend it on the public interest, including spending it on endowment works.